Simplified thermal lattice boltzmann in incompressible limit - Che Sidik, Nor Azwadi; Takahiko, Tanahashi (World Scientific Publishing, 2006)
In this paper, an incompressible thermohydrodynamics for the lattice Boltzmann scheme is developed. The basic idea is to solve the velocity field and the temperature field using two different distribution functions. A derivation of the lattice Boltzmann scheme from the continuous Boltzmann equation is discussed in detail. By using the same procedure as in the derivation of the discretised density distribution function, we found that a new lattice of four-velocity model for internal energy density distribution function can be developed where the viscous and compressive heating effects are negligible. This model is validated by the numerical simulation of the porous plate couette flow problem where the analytical solution exists and the natural convection flows in a square cavity.